ANALISIS VISUAL STORYTELLING DALAM FILM NKCTHI : MENCIPTAKAN CINTA DAN KEHARMONISAN MELALUI NARASI DAN SINEMATOGRAFI - Abdul Ghoni, Salman Fadhilah; Resmisari, Ganis (INSIDE : Jurnal Desain Interior, 2025)
Harmony within a family, especially communication between parents and children, plays a crucial role in fulfilling a child's basic need for acceptance and parental love. The film “Nanti Kita Cerita Tentang Hari Ini” (NKCTHI) attempts to depict this issue through the technique of visual storytelling. This study aims to analyze how the The Mountain visual storytelling approach (a method of crafting a story with an emotional conflict peak in the middle, resembling a mountain shape) and visual narrative elements such as narration techniques, editing, coloring, and cinematography in the film NKCTHI effectively portray family emotional conflicts in a close and realistic manner. Using a qualitative-descriptive method, the analysis examines each scene and visual element in the film. The findings reveal that the visual storytelling approach successfully provides a tangible depiction of the importance of openness within families, while affirming that films can serve as an effective medium for conveying social and moral values.